Das dritte Petersburger Gymnasium - Uspenskaja, Anna (Hyperboreus, 2014)
The paper deals with the history of the 3rd St Petersburg Grammar school (founded in 1726 as the school at the Academy of Sciences and transformed into Russia’s ﬁrst Classical grammar school in 1811). The history of the School (regarded as “the most Classical”) demonstrates vividly changes through which Classical education in Russia went: the adoption of the European educational system (“Uvarov’s classicism”), in the early 19th century, D. Tolstoy’s and other reforms in the 2nd half of this century, and the discredit of the Classical education in the early 20th century. The paper focuses on the views on Classical education of the Russian poet Afanasij Fet and surveys the recollections of the School alumni, including some in verse by D. S. Merezkovskij.